TOURISM IN FUNCTION OF DEVELOPMENT OF THE REPUBLIC OF SERBIA - ?ourism as a Generator of Employment - Mićović, Andrej (Hotel and Tourism Management, 2021)
Conclusions of the 4th International Scientific Conference held at the Faculty of Hotel Management and Tourism in Vrnja?ka Banja, May 30th – June 1st, 2019